PENERAPAN COOPERATIVE LEARNING MODEL: CIRC UNTUK MENINGKATKAN KETERAMPILAN MEMBACA SISWA SEKOLAH DASAR - Murtono, (Pendidikan Sekolah Dasar, 2011)
The reading comprehension skill of the students of SD 03 Demaan Kudus was quite insufficient before the classroom action research is conducted. There are factors for this insufficiency: the traditional model of learning that is less effective and tends to make the students boring; most students are less motivated in learning and less interested in reading subject; the technique that uses direct evaluation during the process of learning, in which students are directly assigned to read which make such process boring and less interesting for the students; most students are passive during the learning process; and the achievement for the reading comprehension subject is not satisfying. Based on this condition, the action research is conducted. The cooperative learning model, CIRC model is applied in the first cycle and it shows that result is not satisfying both from cognitive and affective standpoints. This is because the model is still new both for the teacher and the students; therefore, it is not effectively applied. The research moves to the second cycle. The result of this cycle shows that the achievement of the students is getting better and quite satisfying. This is due to the fact that both the teacher and the students are successful in applying the model.